Hubungan antara penerimaan, kesediaan, logistik dan insentif dengan penglibatan program pendidikan pencegahan dadah dalam kalangan keluarga B40 - Ezarina Zakaria; Fauziah Ibrahim; Nazirah Hassan (Penerbit Universiti Kebangsaan Malaysia, 2020)
This article attempts to discuss findings from a survey study. The study aims to identify level of participation in drug education prevention program among the B40 families. It investigates four factors affecting their participation in the program, including family acceptance towards ex-drug abusers, the readiness to participate in the program and the logistic and incentive access. A total of 295 families were randomly selected to participate in the study. Participation in the program from the families is found to be at a moderate level. Findings suggest there is a significant relationship between their participation in drug prevention education program and their acceptance towards ex-drug abusers, their readiness to participate and the logistic and incentive access. The findings reflect the decrease participation in the program due to the lack of logistic and incentive access provided by the program. The study also highlights the implications for improving agency's networking through outsourcing the drug prevention education program.